Community Empowerment in Improving the Welfare of Hiyung Chili Farmers Groups in Hiyung Village, Tapin District, Indonesia - Saifudin, Saifudin; Latifah, Noor; Al Syahrin, M Najeri; Badrian, Badrian (Technium Social Sciences Journal, 2023)
This study aims to analyze the Community Empowerment of the Hiyung Chili Farmers Group in Hiyung Village, Tapin Tengah District, Tapin Regency, Indonesia. This research uses a descriptive research type which is analyzed using a qualitative approach. Research informants are the head of development and development of village economic enterprises, head of field horticulture, agricultural extension workers, heads of farmer groups, and members of farmer groups in the Tapin District. The results of this study show that the Community Empowerment of the Hiyung Chili Farmers Group in Hiyung Village, Tapin Tengah District, Tapin Regency is empowered, which is, seen in the indicators resource good enough. The socio-economic infrastructure is good, as can be seen from the construction of farm roads, chili processing houses, and the main road which has been repaired. In terms of natural resources, it has supported farming activities, namely fertile land, large areas of land, and sufficient water. Indicator Knowledge and skills farmer already Enough Good. The average farmer’s formal education is elementary school graduates. Farmers often hold discussions related to chili farming problems. Farmers helping each other in solving problems is already good. Indicator Opportunity This is quite good as can be seen from the ability of farmer groups to collaborate with various parties so that they can open up opportunities to increase income. Farmers must further increase their knowledge and skills regarding agriculture and entrepreneurship through normal education such as attending various trainings held by the government and the private sector related to the world of agriculture and entrepreneurship.